Genetic sources of resistance to root rots chicory - T. Yu. Polyanina; I. V. Smirnova; O. M. Vyutnova; E. A. Evseeva; N. A. Ratnikova; I. A. Novikova (Овощи России, 2021)
Relevance. One of the significant problems in the technology of obtaining root chicory is the protection of root vegetables from the defeat of root rots. The most common lesions of root vegetables chicory various pathogenic species of fungi causing phomosis (Phoma rostrupii Sacc.), gray rot (Botrytis cinerea (R.) Fr.J), wet bacterial rot (Erwinia carotovora (Jones) Holt.). An important place in solving this problem is the breeding of new varieties that are resistant to major diseases and adapted to the conditions of cultivation in the soil-climatic conditions of the chicory-seeding zone. This requires, first of all, to determine the range of donor varieties of the sign of resistance to root rots, both during the growing of culture, and during long-term storage.Material and methods. In 2018-2020, studies were carried out to assess gene sources of different ecological and geographical origin (including against a provocative background) in the Non-Black Earth Zone of the Russian Federation and to isolate donors of resistance to root rot from them. Research on the Rostov Vegetable experimental station on chicory.Results. Studies have shown that the defeat of root vegetables chicory root rots genetic sources were very different from each other, so Harpachi, Luxor did not affect the. root rots neither on the usual nor on provocative backgrounds.